The importance of functional nutrition, and its role during breast cancer treatment (Research, Society and Development, 2022)
Functional foods, when consumed properly, possibly play a fundamental role in addition to nutritional value, which will help in the prevention and treatment of autoimmune, chronic non-infectious diseases, thus reducing the risk of disease proliferation. Flaxseed is a protective vegetable that has been scientifically shown to be characterized by its importance with beneficial effects against breast cancer and others, which has a high prevalence in the world population, preventing the development of the pathology or through prevention so that they can adopt behaviors healthy. Thus, the present work describes the main components of flaxseed and its active effects that can contribute to the prevention and control of breast cells. For this, a bibliographic review of the literature in scientific articles, studies in official bodies in the search in databases published between 2009 to 2021. The complexity of this treatment through functional nutrition is a challenge, where you will have a planning and strategies so that they can adopt healthy behaviors.